Otimização dos parâmetros de usinagem de acabamento através da rugosidade no torneamento do aço ABNT 4340 - Muhl, Ricardo Teran (2019)
This study evaluates the effect of the machining parameters, cutting speed, feed rate, cutting depth and tool radius, over the roughness parameters Ra, Rz and Rku, during the dry turning of hardened steel. The material used was ABNT 4340 with a hardness of 55 HRc. The machining was performed using mixed ceramic tools (70% Al2O3 + 30% TiC) with "S" edged microgeometry. The experiments were planned and analyzed with the technique of full factorial planning, using the Response Surface Methodology, where it was possible to determine the relationship between the input factors and the output data. The results observed during the tests showed that the feed rate was the parameter that exerted the greatest influence on the roughness Ra, followed by the tool tip radius. The cutting speed showed little significance. When analyzing the Rz roughness, it is possible to observe that all the factors present statistical significance. For the Rku parameter, the only significant factor is the feed rate. As a final result, the optimal cutting parameters for the ideal roughness condition were delineated within the analyzed ranges.